MODERNIZATION OF THE HIGHER EDUCATION SYSTEM IN UKRAINE IN THE CONTEXT OF IMPLEMENTING AUTONOMY OF HIGHER EDUCATION INSTITUTIONS - Деркач, Олександр (Київський національний університет імені Тараса Шевченка, 2023)
B a c k g r ou nd . The essence of autonomy of higher education institutions has been considered, and an overview and analysis of the problems that have accumulated in the domestic higher education system have been conducted. Overcoming these problems has shown positive results, and certain recommendations have been provided regarding the formation of university autonomy as a means of addressing systemic issues in domestic higher education. An overview and analysis of the problems that have accumulated in the domestic higher education system have been conducted. It is noted that these problems can be overcome through the modernization of higher education in the direction of autonomy. It is empha- sized that positive results can be achieved by ensuring greater freedom in university governance, implementing principles of transpar- ency, openness, and social responsibility. The purpose of the article is to investigate the state of implementing autonomy in domestic higher education institutions in the pro- cess of modernizing the higher education system in Ukraine. Re su lt s . Building a modern higher education system that can compete with global systems requires the introduction of innovative approaches, flexible training programs, and the promotion of students' creativity and self-realization. In addition, it is important to provide adequate support and funding for higher education to ensure quality infrastructure development, modern technologies, research, and support for talented scientists. C onc lu si on s . So, here's the deal, modernization of higher education in Ukraine towards autonomy is a complex and long-term process that requires careful analysis, planning, and involvement of all stakeholders. It is important to create effective governance mechanisms, ensure openness and transparency of processes, and engage the general public in dialogue and decision-making.

Вступ . Розглянуто сутність автономії закладів вищої освіти, проведено огляд та аналіз проблем, що накопичилися у вітчизня- ній системі вищої освіти. Подолання цих проблем дало позитивні результати, надано певні рекомендації щодо формування універси- тетської автономії як засобу розв'язання системних проблем вітчизняної вищої освіти. Здійснено огляд та аналіз проблем, що накопичилися у вітчизняній системі вищої освіти. Зазначається, що ці проблеми можна по- долати шляхом модернізації вищої освіти в напрямі автономізації. Наголошується, що позитивних результатів можна досягти шля- хом забезпечення більшої свободи в управлінні університетом, впровадження принципів прозорості, відкритості та соціальної відповідальності. Мета статті – дослідити стан реалізації автономії у вітчизняних закладах вищої освіти у процесі модернізації системи вищої освіти в Україні. Рез у л ь тат и . Побудова сучасної системи вищої освіти, здатної конкурувати з глобальними системами, потребує впровадження інноваційних підходів, гнучких програм навчання, сприяння творчості та самореалізації студентів. До того ж, важливо забезпечити адекватну підтримку та фінансування вищої освіти для забезпечення розвитку якісної інфра- структури, сучасних технологій, наукових досліджень і підтримки талановитих науковців. Висновк и . Отже, модернізація вищої освіти в Україні в бік автономії – це складний і довготривалий процес, який потребує рете- льного аналізу, планування та залучення всіх зацікавлених сторін. Важливо створити ефективні механізми управління, забезпечити відкритість і прозорість процесів, залучити широку громадськість до діалогу та прийняття рішень.
МОДЕРНІЗАЦІЯ СИСТЕМИ ВИЩОЇ ОСВІТИ В УКРАЇНІ В КОНТЕКСТІ ВПРОВАДЖЕННЯ АВТОНОМІЇ ЗАКЛАДІВ ВИЩОЇ ОСВІТИ